Effects of short-range disorder upon electronic properties of a-SiC alloys - Ivashchenko, V.I.; Shevchenko, V.I. (Applied surface science, 2001)
Molecular dynamics (MD) simulations, based on an empirical potential approach, have provided detailed information about chemical ordering and the structural short-range order in stoichiometric amorphous silicon carbide (a-SiC). Recursion band structure calculations based on amorphous geometries obtained from the MD simulations have enabled to establish the mechanism of an influence of homopolar bonds, three-fold (T 3) and five-fold (T 5) coordinated defects, strongly disordered four-fold coordinated sites and atoms, which are first nearest neighbors (FNN) of these defects (T 4) on the distribution of electronic states. We have found that electronic states at the middle of the gap can be associated with these kinds of defect with the exception of antisite defects (like-atom or homopolar bonding). It is the problem of chemical ordering in the stoichiometric silicon–carbon alloy that is the main subject of the present work. In contrast to crystalline SiC, in a-SiC, the resonance states at the valence band top, associated to Si–Si homonuclear bonds, split for the low symmetry of the amorphous surrounding, which gives rise to the additional split states at the band gap bottom. As a result, in the amorphous material, the decrease of a degree of chemical ordering is accompanied by narrowing the band gap.